P-D7 Structural mimicry of the antigen binding modes of rhesus macaque and human anti-gp120 V3 antibodies. (January 2016) - Pan, Ruimin; Jia, Manxue; Li, Liuzhe; Robinson, James; Zolla-Pazner, Susan; Gorny, Miroslaw; Wu, Xueling; Kong, Xiang-Peng
Abstract : Background: Nonhuman primates (NHPs), such as rhesus macaques, are currently the best preclinical models for studying HIV vaccines. The details of how NHP Abs can mimic human Abs will be useful in evaluating NHP Ab responses to HIV vaccine candidates. The extensive knowledge of the antigen binding modes of anti-V3 Abs allows a structural comparison of NHP and human Ab binding modes. Methods: We have crystallized and determined the epitope complex structures of rhesus macaque anti-V3 monoclonal Abs (mAbs) 2.10A (encoded by a VH5 family gene and derived from an animal infected with SHIV SF162P4) and P2A10 and P2E3 (encoded by VH3 family genes and from an animal infected with SHIV SF162P3N). These structures were compared to the Ab-epitope interactions of human anti-V3 mAbs encoded by the equivalent human genes. Results: Human anti-V3 mAbs preferentially use VH5, VH1 and VH3 family genes with the antigen binding sites resembling either a cradle or ladle, respectively, as previously described. Similarly, rhesus macaque mAb 2.10A utilizes the cradle-binding mode while mAbs P2A10 and P2E3 use the ladle-binding mode. Additionally, the amino acids encoded by both human and macaque VH3 and VH5 family germline genes are critical for shaping the antigen binding sites. Thus, key elements in the antigen-Ab interactions are preserved between human and rhesus macaque mAbs. Conclusions: The antigen binding modes of human and rhesus macaque mAbs targeting HIV-1 gp120 V3 epitopes were found to be structurally extremely similar at the atomic level.